Accurate detection of the edges of a room In a photograph - Lim, Dao Wei (2019)
This report will address 4 main components of the project, the objectives, methodology, results and lastly the conclusion. The objective of this project is to develop a program for extracting the 3-D geometry of a room from a 2-D photograph by first addressing the core problem of edge detection and the noise that comes with the photographs. In order to achieve the above mentioned objective, the methodology is broken down into 3 main phases, pre-processing, the “walking” method and post-processing which will be further elaborated in Chapter 3 of the report under Methodology. The program will be tested on an image with the results being reflected in Chapter 4 of the report. Together with these results, the problems or obstacles encountered whilst developing the program will be addressed as well. Lastly, the final chapter of the report will include the conclusion together with discussions for future works and what can be done to further improve the program.